Consumers’ attitudes towards animal suffering: A systematic review on awareness, willingness and dietary change - Fonseca, R. P.; Sanchez-Sabate, R. (International Journal of Environmental Research and Public Health, 2022)
Planetary and human health depend on Westerners' ability to reduce meat consumption. Meat production degrades the environment while excessive meat intake is associated with cancer and cardiovascular disease, among others. Effective reasons and motivations are needed for consumers to change their diet. The fact that modern animal agriculture inflicts a great deal of pain on animals from their birth to their slaughter, animal welfare/suffering may drive consumers to meat curtailment. This systematic review examined a total of 92 papers to ascertain consumers’ awareness of the pain animals experience in animal agriculture, as well as consumer attitudes towards meat reduction due to animal welfare. Results show consumers have low awareness of animal agriculture. Awareness of animal agricultural practices and animal sentience is associated with increased negative attitudes towards animal suffering. Animal suffering due to farming practices, transportation, slaughter, and animal sentience is appealing for reducing meat consumption, and even dietary change in the short term. There is also evidence that animal suffering may be a more compelling motivation for consumers' willingness to change their diet than for health or environmental reasons. Therefore, increasing consumers’ awareness of animal suffering in meat production is paramount to contributing to reduced pressure on the environment and improved human health.